2019
DOI: 10.1007/s40430-019-2110-3
|View full text |Cite
|
Sign up to set email alerts
|

Research of transient rotor–stator interaction effect in a mixed-flow pump under part-load conditions

Abstract: In order to analyze the unsteady flow characteristic and the pressure fluctuation features of mixed-flow pump caused by the interaction between the impeller and guide vanes under part-load conditions, the unsteady flow field in the mixed-flow pump was numerically simulated based on the standard k-ε turbulence model. The pressure distribution and the velocity distribution in the rotor-stator interaction (RSI) zones were acquired, and the time domain and frequency domain of the pressure fluctuation were emphatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In one related work, Pei et al [11] introduced the pressure pulsation intensity coefficient and peak pressure coefficient, to provide a new way for evaluating the pressure pulsation. Similarly, Cao et al [12] observed that the higher the amplitude of pressure pulsation, the larger the distribution range of frequency domain and the larger the frequency component in rotor-stator interaction zones. Shi et al [13] noticed that the blade angle deviation led to an uneven pressure change in the impeller passage and substantially affected the safe and stable operation of axial flow pumps.…”
Section: Introductionmentioning
confidence: 77%
“…In one related work, Pei et al [11] introduced the pressure pulsation intensity coefficient and peak pressure coefficient, to provide a new way for evaluating the pressure pulsation. Similarly, Cao et al [12] observed that the higher the amplitude of pressure pulsation, the larger the distribution range of frequency domain and the larger the frequency component in rotor-stator interaction zones. Shi et al [13] noticed that the blade angle deviation led to an uneven pressure change in the impeller passage and substantially affected the safe and stable operation of axial flow pumps.…”
Section: Introductionmentioning
confidence: 77%
“…At present, numerical simulation and experiments are dominant research approaches of RSI, mainly revealing the flow field structure and the pressure pulsation characteristics by time-frequency domain analysis. Cao et al and Rodriguez et al [12,13] proceed research to capture the unstable flow properties and the pressure pulsation features induced by RSI between the guide vanes and impeller of centrifugal pump, obtaining the conclusion that the dominant frequency of pressure pulsation is roughly consistent with the blade passing frequency and the number of peaks and valleys of pressure pulsation curve is coincident with blades. Also, Issa et al [14] explored the influence of the RSI on the steady and unsteady radial force in a centrifugation between impeller blade and volute tongue.…”
Section: Introductionmentioning
confidence: 99%
“…e mixed-flow pump is a common hydrodynamic rotating mechanical device widely used in engineering [1][2][3][4][5] due to its moderate head and the capacity of transporting a larger flow rate. As the semiopen impeller is usually used in the mixed-flow pump, the internal flow fields of a mixedflow pump are extremely complex and totally turbulent, including tip leakage flow (TLF) [6,7], back flow [8], and vortex shedding from the blade tip region [9], as well as the RSI between the impeller and guide vane [10]. Among the all complex flows, the TLF, driven by the high-pressure gradient between the blade pressure surface and suction surface, will affect most of the flow fields of impeller flow channels and make the pump efficiency drop a lot [11].…”
Section: Introductionmentioning
confidence: 99%